Heresy in the Siberian way: publishing activities of non-traditional religions, sects, dogma in Siberia and the Far East (90s of the XX - 10s of the XXI centuries) - A. L. Posadskov (Библиосфера, 2017)
Since the early 1990s non-traditional religions were widespread in Siberia and the Far East, and across Russia, among which there was a large number of totalitarian sects and destructive cults. The reason for the phenomenal success of previously unknown religious and occult teachings has been the spiritual vacuum that occurred in the country after the Communist ideology fall. Most of the new denominations launched in Russia publishing, which by the second decade of the XXI century was carried on by several dozen communal or sectarian publishers. In Siberia and the Far East the most active sects in publishing were the following: Protestant Church of Christ, Baha'i Faith followers, Krishna consciousness regional societies (in particular, the residents of Vladivostok), «Pleiadinas» sects («Ascended Masters» teachings). These sectarian creeds nave been brought into the country, however, and nowadays pseudo-religious cults are created in Russia, which carry a large destructive potential for the Russian society and its cultural traditions. They are Neo-pagans, the Marian center and a number of sects, whose activities began in Siberia: All-Russian movement «To God’s Rule!», The Church of the Last Testament of Vissarion Christ, etc. These cults had in Siberia and the Far East extensive publishing practices editing books, brochures, magazines, newspapers. «Pleiadinas» sect organized in Siberia edition of the monthly magazine «World Channeling» (Novokuznetsk), created two publishing houses: «Star of Freedom» (Novosibirsk) and «SiriuS» (Omsk). The Marian center used printing district offices of Kemerovo region for its production activity. Neo-pagans had publishing houses «Asgard’», «Arcor» and «Russian Truth» in Omsk. The article analyzes all these publishing organizations’ products. The ruinous effects of sectarian publishing activities distribution in the Russian regions is obvious. Its effect reduction will depend on the speed of eliminating the crisis in the spiritual sphere of our society.